Answer:
3/3=1
Step-by-step explanation:
Answer:
Kelsey is correct.
Step-by-step explanation:
One of the rules when solving an equation is that you need to isolate the variable, meaning that it just needs to be x by itself. To do that, you would need to start by subtracting 6. If you were to divide by 3 first, the answer would be twice what it should be.
Answer:
Step-by-step explanation:
it is a and j
Hello :
<span> y=-6(2.5-x)(x-5.5) = -6(2.5x -13.75 -x² +5.5x)
y = -6(-x²+8x -13.75)
y = 6x²-48x+82.5
note :
if f(x) = ax²+bx +c the vertex is the point : ( -b/2a ; f(-b/2a))
a=6 b=-48 c = 82.5 .......calculate
-b/2a = -(-48)/2(6)= 4
f(4) =6(4)²-48(4)+82.5 =96 - 192 +82.5 = -13.5</span>
Answer:
c 150
Step-by-step explanation:
hopefully this will help you out